Hydroisomerisierung von langkettigen n‐Alkanen an bifunktionellen Zeolith‐Katalysatoren1. Issue 7 (23rd March 2017) - Zschiesche, Christopher; Himsl, Dieter; Rakoczy, Rainer; Reitzmann, Andreas; Freiding, Jens; Wilde, Nicole; Gläser, Roger
Abstract: The hydroisomerization of a C10  – C13 n ‐alkane mixture was investigated over six bifunctional platinum‐containing zeolite catalysts with 10‐ and 12‐membered ring pore systems. The catalysts with 12‐membered‐ring zeolites are more active than those with 10‐membered‐ring zeolites. In Contrast, higher yields of the desired mono‐branched isomers are obtained on the 10‐membered‐ring zeolites due to shape‐selectivity effects. For the 10‐membered‐ring zeolites, higher reaction temperatures are required for achieving the maximum isomer yields, which leads to more cracking products compared to the 12‐membered‐ring zeolites.